Risk factors for incident heart failure with preserved or reduced ejection fraction, and valvular heart failure, in a community-based cohort - Gong, F.; Jelinek, M.; Castro, J.; Coller, J.; McGrady, M.; Boffa, U.; Shiel, L.; Liew, D.; Wolfe, R.; Stewart, S.; Owen, A.; Krum, H.; et al. (2018)
Background: The lack of effective therapies for heart failure with preserved ejection fraction (HFpEF) reflects an incomplete understanding of its pathogenesis. Design: We analysed baseline risk factors for incident HFpEF, heart failure with reduced ejection fraction (HFrEF) and valvular heart failure (VHF) in a community-based cohort. Methods: We recruited 2101 men and 1746 women =60 years of age with hypertension, diabetes, ischaemic heart disease (IHD), abnormal heart rhythm, cerebrovascular disease or renal impairment. Exclusion criteria were known heart failure, left ventricular ejection fraction <50% or valve abnormality >mild in severity. Median follow-up was 5.6 (IQR 4.6-6.3) years. Results: Median time to heart failure diagnosis in 162 participants was 4.5 (IQR 2.7-5.4) years, 73 with HFpEF, 53 with HFrEF and 36 with VHF. Baseline age and amino-terminal pro-B-type natriuretic peptide levels were associated with HFpEF, HFrEF and VHF. Pulse pressure, IHD, waist circumference, obstructive sleep apnoea and pacemaker were associated with HFpEF and HFrEF; atrial fibrillation (AF) and warfarin therapy were associated with HFpEF and VHF and peripheral vascular disease and low platelet count were associated with HFrEF and VHF. Additional risk factors for HFpEF were body mass index (BMI), hypertension, diabetes, renal dysfunction, low haemoglobin, white cell count and ß-blocker, statin, loop diuretic, non-steroidal anti-inflammatory and clopidogrel therapies, for HFrEF were male gender and cigarette smoking and for VHF were low diastolic blood pressure and alcohol intake. BMI, diabetes, low haemoglobin, white cell count and warfarin therapy were more strongly associated with HFpEF than HFrEF, whereas male gender and low platelet count were more strongly associated with HFrEF than HFpEF. Conclusions: Our data suggest a major role for BMI, hypertension, diabetes, renal dysfunction, and inflammation in HFpEF pathogenesis; strategies directed to prevention of these risk factors may prevent a sizeable proportion of HFpEF in the community. Trial registration number: NCT00400257, NCT00604006 and NCT01581827.